ChemInform Abstract: Chemotherapy of Leishmaniasis. Part 11. Synthesis and Bioevaluation of Novel Isoxazole Containing Heteroretinoid and Its Amide Derivatives. Issue 11 (8th March 2013) - Suryawanshi, S. N.; Tiwari, Avinash; Chandra, Naveen; Ramesh, Ramesh; Gupta, Suman
Abstract Heteroretinoid (Ib) and its amide (Ic‐i) are synthesized and screened for their in vivo antileishmanial activity against Leishmania donovani in hamsters.